Proyecto para la creacion de un canal de televisión publica administrado por el gobierno autónomo descentralizado del Cantón El Empalme provincia del Guayas a partir del periodo 2012 - Basurto Carranza, Fatima Jacqueline (2012)
One of the measures, the government's most important is that public institutions, working with the motto of "transparency", ie activities by the aforementioned public, can be observed by the citizens of each locality. It is for this reason that we propose the creation of a television channel run by the Autonomous Government of the Canton Decentralized the joint through a project approach feasibility, market studies, economic and financial, for having an important tool within the National Secretary of Planning and Development is sustained financial assessment an alternative proposal Senplades format. The results generated in this investigation determined that: The highest percentage of the population is reported GAD activities Canton Splicing through television media. Furthermore 46% of the population is interested in news programs or news, likewise 38% of respondents considered essential the creation and installation of a television channel, also 66% of the surveyed population believes that the most suitable for accountability and control is through television. In summarythe projecthas proven feasible, the impactgeneratedbythe communityof Cantonsplicing, plus the investment isself-financedwith fundsbudgetedby theGAD, also the project will createan item ofincomeforself, proceeds from the saleofspacesthat can be foundavailableto external users.